Wireless Smoke Detector With Alarm System - Mubasyir , Azizan (UTeM, 2008)
Smoke detectors save hundreds of lives and prevent severe property damage every year. A more efficient warning system, along with a more effective detection system could provide an even safer environment. This project has resulted in the successful implementation of a Wireless Smoke Detector with Alarm System. The alarm incorporates wireless communications, multiple detection methods, constant regulated power, lighting and a remote control. These features are interfaced through the use of a microprocessor. The Wireless Smoke Detector with Alarm System has the potential to detect different frre hazards and then spread the warning through a wireless system, turning on lights and alarms. If the warning turns out to be false, then the remote can be used to turn off the alarms and lights. The wireless network also has the capability of detecting a non-operational alarm. With this in mind and through the use of a constant power source the risk of having a faulty alarm is dramatically reduced. Hence, the Wireless Smoke Detector with Alarm System is a safe and convenient device that is marketable at a reasonable price for a large market. The concept of this product has several possibilities for future extensions and upgrades.